Pelatihan Kewirausahaan Digital Berbasis Kemitraan dalam Meningkatkan Kemandirian UMKM (Pengabdian di Desa Simpang Jaya - Juli Kabupaten Bireuen) - Saleh, M.; Musrizal, Musrizal; Sulaiman, Munawar; Fajri, Riyadhul; Erfan Syah, Muhammad (LPPM Umuslim, 2024)
This article is a descriptive report on service activities in the form of a digital entrepreneurship training program implemented by MSME administrators in Simpang Jaya Village, Juli District, Bireuen Regency, Aceh. This training program is a service activity for Bireuen Almuslim University lecturers carried out at the Simpang Jaya Gampong Digital Community (RKDG), aimed at equipping local micro, small and medium enterprises (MSMEs) with the skills and knowledge needed to develop in the digital economy. Training covers a wide range of topics, including website and online store creation, search engine optimization (SEO), social media management, and digital advertising strategies. Assistance is also provided in analyzing the effectiveness of the program to empower MSMEs, evaluating participants' perceptions of training output, and exploring their contribution to village economic development. The results of the evaluation, in general, activities were carried out according to the objectives, and participants felt helped, both in terms of knowledge, skills and insight into how to do digital or online entrepreneurship.